A new methodology to predict damage tolerance based on compliance via global-local analysis - Gilberto Gomes; Thiago Arnaud A Oliveira; Alvaro Martins Delgado Neto; Luciano Mendes Bezerra (Fracture and Structural Integrity)
Over the years several design philosophies to address fatigue have been developed trying to combine structural safety and economy with aircraft manufacturing and operating processes. The safe-life approach consists of designing and manufacturing an aeronautical structure to be safe throughout its useful life. This approach results in factors that oversize structural elements to prevent possible failure and evidently incurs high design costs. Alternatively, a damage tolerance concept-based approach assumes that the structure, even when damaged, is able to withstand the actions for which it was designed until the detection of a crack due to fatigue or other defects during its operation. This research proposes a new methodology to address the damage tolerance problem in which two-dimensional global-local analysis at different levels of external requests will be made by means of compliance, aimed at finding a relationship between fatigue life and the Paris constant. Moreover, the study uses the BemCracker2D program for simulating two-dimensional crack growth. This methodology has proved to be an efficient alternative applicable to damage tolerance analysis